Frequencies of CD33+CD11b+HLA-DR–CD14–CD66b+ and CD33+CD11b+HLA-DR–CD14+CD66b– Cells in Peripheral Blood as Severity Immune Biomarkers in COVID-19 - Alberca, Ricardo Wesley; Andrade, Milena Mary de Souza; Branco, Anna Cláudia Calvielli Castelo; Pietrobon, Anna Julia; Pereira, Nátalli Zanete; Fernandes, Iara Grigoletto; Oliveira, Luana de Mendonça; Teixeira, Franciane Mouradian Emidio; Beserra, Danielle Rosa; de Oliveira, Emily Araujo; Gozzi-Silva, Sarah Cristina; Ramos, Yasmim Álefe Leuzzi; et al. (Frontiers in Medicine, 2020)
Common clinical features of patients with Coronavirus disease-2019 (COVID-19) vary from fever, to acute severe respiratory distress syndrome. Several laboratory parameters are reported as indicators of COVID-19 severity. We hereby describe a possible novel severity biomarker for COVID-19, characterized as a population of CD11b+CD33+HLA- cells, that can be further divided into CD14+ mononuclear cells and CD66b+ polymorphonuclear cells.